A Lacanian Reading of Select Stories from Samrat Upadhyay’s Arresting God in Kathmandu - Sharma, Chaandani (NPRC Journal of Multidisciplinary Research, 2025)
Background: Samrat Upadhyay’s Arresting God in Kathmandu is a foundational work in Nepali fiction in English, often analyzed through postcolonial and diasporic lenses. While critics have noted its exploration of sexuality and the tension between tradition and modernity, a significant gap exists in applying a psychoanalytic framework to understand the fundamental drivers of the characters' motivations and psychological fragmentation.Objective: This study aims to perform a Lacanian psychoanalytic reading of two stories from Upadhyay’s collection—"The Limping Bride" and "This World." Its primary objective is to examine how the characters' desires are rooted in a constitutive "lack," how their pursuit of an ever-displacing "object of desire" leads to psychological fragmentation, and why they ultimately acquiesce to the societal "Symbolic Order."Methods: The research employs a qualitative textual analysis, using the theoretical framework of Jacques Lacan's psychoanalytic registers—the Imaginary, the Symbolic, and the Real. The stories are categorized thematically to provide a focused examination: "The Limping Bride" is analyzed through the theme of infidelity, and "This World" through identity crisis and the idealization of the Other.Analysis: The analysis reveals that characters like Hiralal ("The Limping Bride") and Jaya and Kanti ("This World") are trapped in a cycle of desire driven by a foundational lack. Their attempts to achieve wholeness through an idealized Other (the Imaginary) are consistently thwarted as the object of desire is perpetually displaced. This internal conflict, set against the rigid norms of Nepali society (the Symbolic), results in profound psychological fragmentation, which is often precipitated by a traumatic encounter with an inassimilable truth (the Real).Conclusion: The study concludes that Upadhyay’s characters are emblematic of a postmodern psyche caught between traditional values and modern, individualistic desires. Their futile pursuit of fulfillment highlights the Lacanian axiom that desire is inherently metonymic and insatiable. Despite their rebellions, their ultimate submission to the Symbolic Order underscores the powerful internalization of societal laws, revealing a profound commentary on the human condition within a rapidly evolving socio-cultural landscape.Implementation: The findings of this research contribute to the critical discourse on Upadhyay’s work, moving it beyond established thematic readings. This Lacanian framework can be implemented in further analyses of South Asian and diasporic literature to explore universal psychological conflicts within specific cultural contexts. It also provides a valuable model for literary scholars and students to deconstruct character motivation and societal conflict in narrative fiction.